GREAT MISSION OF AN INTELLIGENT MUSLIM IN KARAN JOHAR’S MY NAME IS KHAN MOVIE (2010): A HUMANISTIC PSYCHOLOGICAL APPROACH - SETIYANA, AGUSTIN ARUM (2011)
This research paper elaborates the motives underlying the great mission of Khan in My Name is Khan Movie which are analyzed through a humanistic psychological approach. The objective of the research based on its structural elements and to analyze by using humanistic psychological approach. This research belong to qualitative research. The type and the data source which are used, namely primary and secondary data. The primary data source is the movie itself. The secondary data sources are taken from books and other sources which support the analysis. The method of the data collection is library research and the technique of the data analysis is descriptive technique. Having analyzing the movie, first, the writer summaries that the structural elements of the movie are united to each other. Second, the writer draws that the major character of the movie can be said as self-actualized person because the characteristics of self-actualization have been portrayed in his personality.